(untitled) (Bangladesh Journal of Microbiology, 2010)
Four isolates of Aspergillus niger (viz., CA16, 14/20, HB3 and 318) were used for citric acid production using sugarcane bagasse as a substrate and sucrose solution as a moistening agent. Using 3 g of sugarcane bagasse as substrate, the highest citric acid production was obtained when 10 ml of 14% sucrose solution was used as moistening agent. Maximum citric acid production was found after 11 days fermentation for all isolates of A. niger. Both sugar utilization as well as citric acid production was found highest in the presence of Prescott salt by A. niger 318 (196.21 ìg/g), followed next by A. niger 14/20 (103.06 ìg/g). However, in absence of Prescott salt both sugar utilization and citric acid production was highest (50.01 ìg/g) by A. niger 14/20. In general, extension of the fermentation (up to 11 days) resulted in an increase in citric acid, total titratable acid and biomass, and decrease in both residual sugar concentrations. Keywords: Citric acid; Solid-state fermentation; Aspergillus niger; Sugarcane bagasse DOI: http://dx.doi.org/10.3329/bjm.v25i1.4664 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 9-12